Grassland on the top - pilot project on a sustainable green roof - Balog, Ágnes (4D Journal of Landscape Architecture and Garden Art, 2013)
Is it possible for a green roof to be in harmony with the landscape? Is it possible to create green roofs primarily from locally native species? Can we use local soils for green roofs? These questions troubled us when planning our ecological dwelling. Eventually, they materialized as an organic part of our pilot project that aimed at re-thinking the practical and theoretical aspects of ecological homes in Hungary. This paper summarizes the experiences and scientific observations on the novel green roof systems of our own building.
Keywords: grassland; sustainable; green roof